2019
DOI: 10.1038/s41598-019-42171-4
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting impacts of precipitation on Mediterranean birds and butterflies

Abstract: The climatic preferences of the species determine to a large extent their response to climate change. Temperature preferences have been shown to play a key role in driving trends in animal populations. However, the relative importance of temperature and precipitation preferences is still poorly understood, particularly in systems where ecological processes are strongly constrained by the amount and timing of rainfall. In this study, we estimated the role played by temperature and precipitation preferences in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 36 publications
(42 reference statements)
2
41
0
5
Order By: Relevance
“…In every region except Africa median con dence scores were 'medium' and in Africa, seven of the ten scorers responded that climate change effects are 'unknown' ( Figure S2 and Supplementary Table 2). Long-term data scarcity limit and confound the demonstration of current climate change effects on pollinators, and available studies are restricted to few taxa such as bumblebees 13 and butter ies 33 .…”
Section: Resultsmentioning
confidence: 99%
“…In every region except Africa median con dence scores were 'medium' and in Africa, seven of the ten scorers responded that climate change effects are 'unknown' ( Figure S2 and Supplementary Table 2). Long-term data scarcity limit and confound the demonstration of current climate change effects on pollinators, and available studies are restricted to few taxa such as bumblebees 13 and butter ies 33 .…”
Section: Resultsmentioning
confidence: 99%
“…While in the spring the effects of higher temperatures were very variable during both the development of immature stages and the adult flight period, in summer they clearly had a negative effect, except in the ravine. During summer, the increase in temperature generally implies an increase in aridity and a reduction in water availability, which has been identified as a key limiting factor for butterfly species in the Mediterranean (Stefanescu et al ., 2011; Herrando et al ., 2019) and for plant-butterfly interactions (Donoso et al ., 2016). In fact, the difference between this negative effect in summer and the neutral effect in spring was more noticeable when we considered the adult flight period (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Climate warming has been suggested as a possible factor underlying these negative trends; recent work has revealed the major role of climate in the dynamics of Mediterranean butterflies and shown the negative impact of increasing temperatures and drought on certain species (e.g. Merrill et al ., 2007; Zografou et al ., 2014; Mills et al ., 2017; Herrando et al ., 2019; Carnicer et al ., 2019). Moreover, given its small surface area, its physical limits as an island and the absence of high mountain ranges, species on Menorca are limited in their capacity to modify their distributions in response to climate change, as occurs in other areas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that vegetation encroachment was more important in warmer areas and so affects butterfly assemblages in typical Mediterranean habitats more severely. Therefore both climatic and landscape changes interact to ensure that butterfly species from Mediterranean habitats exhibit more negative trends (Herrando et al ). All in all, our results indicate that most species in our region cannot cope with global change, which leads to mismatches affecting the overall butterfly assemblage (e.g.…”
Section: Discussionmentioning
confidence: 99%